Business Strategy, Financial Literacy, and MSME Performance: The Moderating Role of Financial Technology - Salsabrina Windi Putri Deffila; Yulistina Yulistina; Desmon Desmon (Studi Akuntansi, Keuangan, dan Manajemen, 2026)
Purpose: This study analyzes the impact of Business Strategy and financial literacy on Micro, Small, and Medium Enterprises (MSME) performance, specifically exploring the modifying role of fintech. Methodology: This study adopted a quantitative approach, gathering data via questionnaires from 150 registered MSME actors in Bandar Lampung. Data analysis was performed using Moderated Regression Analysis (MRA) and path analysis via SPSS to examine the interaction effects of Financial Technology on the relationship between business strategy, financial literacy, and MSME performance Results: The study demonstrates a positive and significant link between business strategy, financial literacy, and the increase in MSME performance and fintech uptake. While fintech exhibits a direct, significant, and positive effect on performance, it fails to significantly strengthen or weaken the existing relationship between business strategy, financial literacy, and MSME performance. Conclusions: Business strategy and financial literacy are key determinants of improved MSME performance in Bandar Lampung, Indonesia. While fintech has been shown to have a positive impact independently, it fails to strengthen the influence of strategy and financial literacy on business performance. Limitations: As the study only examined micro businesses, its conclusions may not apply to small and medium enterprises. These larger MSME categories have different scales, resources and operational characteristics. Contributions: It is crucial for the government to step up training and mentoring for micro- Small, and Medium Enterprises (SMEs) to foster adaptive strategies in the digital economy to improve their performance. MSMEs must commit to developing long-term, non-impulsive strategies and improving financial literacy as prerequisites for optimally leveraging fintech.